Implementation of Science Project-Based STEAM Learning in Increasing Student Creativity in Elementary Schools - Vivi Uvaira Hasibuan; Fitri Yani (Global Education Journal, 2026)
The demands of competence in the 21st century learning era place high-level thinking skills, creativity, and mastery of skills across fields of knowledge as aspects that cannot be ignored in the implementation of higher education. This study aims to explore the application of a project-based learning model that integrates the Science, Technology, Engineering, Art, and Mathematics (STEAM) approach as an effort to foster the creative thinking skills of students of the Elementary School Teacher Education Study Program (PGSD) in designing natural science teaching aids (IPA) for the elementary education level. The research method used was a one-shot case study involving 20 students as participants. Teaching and learning activities are designed in the form of a project to make teaching aids based on used materials that combine the dimensions of science, technology, engineering, art, and mathematics. Data collection was carried out through observation techniques and questionnaire dissemination using creativity assessment instruments that included three main aspects, namely planning, implementation, and evaluation. Data analysis was carried out descriptively using percentage calculation techniques. The results of the analysis showed that overall the level of student creativity was in the very high category, with an average score of 84.67. In detail, the planning aspect obtained a score of 88, the implementation aspect obtained a score of 86, and the evaluation aspect obtained a score of 80. These results indicate that the application of the STEAM-PjBL model is able to facilitate PGSD students in creating science learning products that are characterized by high creativity, contextual, and problem-solving-oriented.